Relationship between pectoralis major stiffness and shoulder extension range of motion - Konrad, Andreas; Reiner, Marina M.; Warneke, Konstantin; Keiner, Michael; Nakamura, Masatoshi; Tilp, Markus (Frontiers in Physiology, 2024)
This study aimed to investigate the correlation between the passive muscle stiffness of the pectoralis major muscle pars clavicularis (PMc) and shoulder extension range of motion (ROM) in both male and female participants. Thirty-nine (23 male/16 female) physically active and healthy participants volunteered in this study. After a standardized warm-up, the PMc stiffness was tested via shear wave elastography at a slightly stretched position (long muscle length) and in a non-stretched position (short muscle length). Additionally, a custom-made device and 3D motion capture assessed the active shoulder extension ROM. We found a significant moderate and negative relationship between shoulder extension ROM and PMc stiffness at long muscle length (rs = −0.33; p = 0.04) but not at short muscle length (r = −0.23; p = 0.17). Additionally, there was no significant difference between male and female participants in the correlation analyses at both elbow angles. The moderate correlation between PMc stiffness at a slightly stretched position and shoulder extension ROM suggests that additionally, other structures such as nerves/fascia stiffness or even stretch tolerance might be factors that can be related to shoulder extension ROM.